Leptin/adiponectin ratio correlates with hepatic steatosis but not arterial stiffness in nonalcoholic fatty liver disease in Japanese population. (February 2020) - Mikami, Kenichiro; Endo, Tetsu; Sawada, Naoya; Igarashi, Go; Kimura, Masayo; Hasegawa, Takuma; Iino, Chikara; Tomita, Hirofumi; Sawada, Kaori; Nakaji, Shigeyuki; Matsuzaka, Masashi; Torok, Natalie J.; et al.
Highlights: Leptin-to-adiponectin (L/A) ratio correlated with hepatic steatosis in NAFLD. Arterial stiffness correlated strongly with age, and weakly with hepatic steatosis. Arterial stiffness was not correlated with L/A ratio in NAFLD. Interleukin-6 correlated with arterial stiffness, and very weakly with L/A ratio. L/A ratio correlated with triglycerides and the ratio of total cholesterol to HDL-cholesterol. Abstract: Background and aims: Cardiovascular disease (CVD) is a leading cause of mortality in nonalcoholic fatty liver disease (NAFLD). The aim of this study was to investigate the relationship of leptin-to-adiponectin (L/A) ratio with hepatic steatosis and arterial stiffness in NAFLD. Methods: The subjects were 871 Japanese adults who participated in a health survey. Dietary intake, body composition, lipid profile, serum interleukin-6 (IL-6), leptin, and adiponectin were analyzed. NAFLD was defined as fatty liver on ultrasonography in the absence of other causes of steatosis. Arterial stiffness was evaluated by the brachial-ankle pulse wave velocity (baPWV). Results: The subjects with NAFLD had a greater body mass index (BMI) and body fat percentage (BFP); a higher intake of daily energy (kcal) and carbohydrates; and a higher prevalence of hypertension, diabetes, and hyperlipidemia. The subjects with NAFLD had higher serum leptin and lower serum adiponectin concentrations and a higher L/A ratio than subjects without NAFLD. The L/A ratio increased with increasing severity of steatosis. The L/A ratio showed positive correlations with BMI and BFP, and a negative correlation with age. Women had higher L/A ratio and BFP levels than men regardless of the presence or absence of NAFLD. There was a weak positive correlation between baPWV and severity of steatosis. BaPWV was strongly correlated with age, while no relation was found between baPWV and L/A ratio. IL-6 level was correlated with baPVW and age, while the correlation between Il and 6 level and L/A ratio was very weak. The L/A ratio was correlated with triglycerides and the ratio of total cholesterol to high-density lipoprotein-cholesterol. Conclusion: L/A ratio and arterial stiffness were associated with the severity of steatosis, whereas there was no correlation between L/A ratio and arterial stiffness in NAFLD. These findings suggest that not only leptin and adiponectin but also other factors might be involved in the pathogenesis for atherosclerosis in NAFLD.